Nomographic Technique Development on Global Warming Material for High School Student Grade Eleven of Literacy Class - Arum, Anjar Desynta; Suprapto, Nadi (International Journal of Active Learning, 2021)
This research aims to describe the media's feasibility in terms of the validity, practicality, and effectiveness of infographic media as student learning media. This type of research develops ADDIE (Analyze, Design, Development, Implementation, Evaluation) model with data collection techniques in the form of media validation sheets given to media expert lecturers and material experts, as validators, and distributing questionnaires online to 100 Unesa physics students as respondents. Validation measurements from expert lecturers and the ability to understand and practice and the media's effectiveness from respondents used a Likert switch. The validation results from the expert lecturers based on the learning aspects, the material aspects, and the media aspects and physics students' responses based on the ability of understanding and practice and effectiveness. The result of the average value shows that the respondents agreed to the media being developed. Based on the results of student responses, the validity test was obtained with a value of r count> r table, so that the media designed was declared valid, and based on the reliability test with a Cronbach's alpha value greater than 0.6, the questionnaire was declared reliable or consistent. It can conclude that the infographic media that develops nomography techniques are conceptually feasible and can be used in the learning of students' scientific literacy.